Research on clustering protocols based on event-driven - Xiaohu Zhao; Chenjun Hu; Qianqian Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to ensure the safety production in coal face, we need to monitor face working conditions and environment information; this paper presents a kind of clustering routing algorithm which is based on event-driven. Under normal circumstances, we improve LEACH protocol to monitor the information on the face; in an emergency, cluster head nodes in the event area will be selected based on events the degree of irritation the node residual energy and the power transmission level. The simulation results show that the agreement can quickly build a temporary path for effective data fusion, and can prolong the network lifetime. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2046